Discrete Events of Ionosomes at the Water/Toluene Micro-Interface - Zhang Jingyan; Huang Linhan; Fang Taoxiong; Du Feng; Xiang Zhipeng; Zhang Jingcheng; Chen Ran; Peljo Pekka; Ouyang Gangfeng; Deng Haiqiang (WILEY-V C H VERLAG GMBH, 2025)
Emulsification is a powerful technique for dispersing one fluid (water or oil) in the form of tiny droplets within an immiscible continuous fluid (oil or water). Hence, emulsion is an essential component of medicine, food, and shampoo, to name a few. An emulsifier, e. g., a surfactant, is normally added inside emulsions to stabilize the water/oil interfaces. Ionosomes, nanoscopic water droplets enclosed solely by an ionic bilayer, in which one layer formed from small and more mobile hydrated ions residing in the inner aqueous side and another layer formed from lipophilic bulky counter-ions riveted tightly in the adjacent outer oil side, were generated and in-situ counted "one at a time" at a polarized water/toluene micro-interface. Chemical polarization through the biphasic distribution of an antagonistic salt proved the proposed ionic bilayer structure of ionosomes. Promotion effect on Li+-ionosomes revealed by single-entity electrochemistry for quaternary ammonium cations with different alkyl chain length and with different concentration sheds new light on the mechanism of ionosomes. Fusion of a Li+-ionosome with the polarized soft micro-interface follows the bulk electrolysis model.